Twin pregnancy with two live fetuses at 11–13 weeks: effect of one fetal death on pregnancy outcome. (6th March 2020) - Cimpoca, B.; Syngelaki, A.; Chi Mu, A.; Savvoulidou, E.; Nicolaides, K. H.
ABSTRACT: Objectives: First, to compare the incidence of single and double fetal death between monochorionic (MC) and dichorionic (DC) twin pregnancies with two live fetuses at 11–13 weeks' gestation and no major abnormalities. Second, to investigate the relationship between gestational age at single fetal death and interval to delivery of the cotwin. Third, to determine the rate of early preterm birth in DC and MC twin pregnancies with two live fetuses and those with single fetal death. Methods: This was a retrospective analysis of prospectively collected data on twin pregnancies undergoing routine ultrasound examination at 11–13 weeks' gestation between 2002 and 2019. The outcome measures, which were stratified by chorionicity, were: first, death of both fetuses at presentation or death of one fetus followed by delivery of a live or dead cotwin within the subsequent 3 days at < 34 weeks' gestation; second, in pregnancies with single fetal death at < 34 weeks' gestation and a live cotwin ≥ 3 days later, the subsequent risk of fetal death and gestational‐age distribution at birth of the cotwin; and, third, the gestational‐age distribution at birth in pregnancies with two live fetuses. Results: The main findings of this study of 4896 DC and 1329 MC twin pregnancies with two live fetuses at 11–13 weeks' gestation were: first, the rate of death of both twins or death of one fetus and delivery of the live or dead cotwin within 3 days was higher in MC than in DC twin pregnancies; second, the rate of single fetal death with a live cotwin ≥ 3 days later was higher in MC than in DC twin pregnancies, but the rate of subsequent cotwin death in MC twin pregnancies was not significantly different from that in DC twin pregnancies; third, in pregnancies with two live fetuses, the rate of early preterm birth was significantly higher in MC than in DC twin pregnancies; fourth, the rate of early preterm birth in pregnancies with single fetal death and a live cotwin ≥ 3 days later was not significantly different between MC and DC twin pregnancies but the rates were substantially higher than in those with two live fetuses; and, fifth, in both MC and DC pregnancies with single fetal death and a live cotwin ≥ 3 days later, there was a significant inverse association between gestational age at death and interval to delivery (mean interval of 19 weeks for death at 15 weeks and mean interval of 2.5 weeks for death at 30 weeks). Conclusions: First, in MC twin pregnancies, the risk of single or double fetal death is higher than in DC twins. Second, in both MC and DC twin pregnancies, the rate of early preterm birth is higher in those with one fetal death than in those with two live fetuses. Third, in both MC and DC twins with one fetal death, the interval to delivery is related inversely to gestational age at fetal death. These data should be useful in counseling parents as to the likely outcome of their pregnancy after single fetal death and in defining strategies for surveillance in the management of these types of twin pregnancy. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.